6(2x-9)=2(6x+5)

Simple and best practice solution for 6(2x-9)=2(6x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2x-9)=2(6x+5) equation:


Simplifying
6(2x + -9) = 2(6x + 5)

Reorder the terms:
6(-9 + 2x) = 2(6x + 5)
(-9 * 6 + 2x * 6) = 2(6x + 5)
(-54 + 12x) = 2(6x + 5)

Reorder the terms:
-54 + 12x = 2(5 + 6x)
-54 + 12x = (5 * 2 + 6x * 2)
-54 + 12x = (10 + 12x)

Add '-12x' to each side of the equation.
-54 + 12x + -12x = 10 + 12x + -12x

Combine like terms: 12x + -12x = 0
-54 + 0 = 10 + 12x + -12x
-54 = 10 + 12x + -12x

Combine like terms: 12x + -12x = 0
-54 = 10 + 0
-54 = 10

Solving
-54 = 10

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| =12x^2-144x+299 | | 16n^2+49=0 | | 2(x+2)+2(x)= | | 2x(x+2)+2(x)= | | (x)(x-1)(x+4)=12 | | 2(8*3x)-7+5x=-(7x*2) | | -2k^2-162=0 | | -26=2y-8(x-y) | | 6b=13b-221 | | 2(8+3x)-7+5x=-(7x-2) | | 11x+12y=13 | | 4(3x+5)=2(9x+16) | | 9x+7=8x | | -2(x+4)+5=6(x+2)+2 | | 5(3x-2y)-(x+6y)= | | -7n^2-488=0 | | X^2+19=33 | | 3(2-a)-4(-6-2a)= | | 4x-5=30 | | 100=4.625 | | 7x^2=0 | | -5x^2-500=0 | | 5(X+2)-2(2X+3)=34-5X | | -174-7z=-13z | | X^3-2x^2-4x+8=0 | | -3(5-9v)=25+7f | | 8(4x+7)=12k-4 | | 2x+5=X-8whatisx | | cosx-sinx=0 | | 8x^3+168x^2-176x=0 | | 7x^2y+4xy^2-6xy+yx= | | 333-5y=8 |

Equations solver categories